2008
DOI: 10.1007/s11095-008-9711-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Dynamic Models of Arthritis Progression in the Rat

Abstract: Purpose This comparison employs mathematical disease progression models to identify a rat model of arthritis with the least inter-animal variability and features lending to better study designs. Methods Arthritis was induced with either collagen (CIA) or mycobacterium (AIA) in either Lewis or Dark Agouti (DA) rats. Disease progression was monitored by paw edema and body weight. Models with production, loss, and feedback components were constructed and population analysis using NONMEM software was employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 30 publications
6
33
0
Order By: Relevance
“…The CIA rat model is the most frequently used experimental model to mimic the human disease with an advantage of a relatively short time-frame and readily measured disease markers [1115]. This CIA model shares many similar disease characteristics with human RA, such as synovial immune infiltration, pannus formation and joint destruction, and it also exhibits many common immunological factors seen in human RA, including rheumatoid factor (RF) and anti-collagen type II (anti-CII) antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CIA rat model is the most frequently used experimental model to mimic the human disease with an advantage of a relatively short time-frame and readily measured disease markers [1115]. This CIA model shares many similar disease characteristics with human RA, such as synovial immune infiltration, pannus formation and joint destruction, and it also exhibits many common immunological factors seen in human RA, including rheumatoid factor (RF) and anti-collagen type II (anti-CII) antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, these are not present in the AIA model [32]. Our previous publication has showed that the CIA Lewis rat model is preferable to the AIA model for PK / PD assessment of RA therapeutics [15], and therefore this animal model was selected in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different PD models, indirect response model I combined with simple feedback model (model A) [23], feedback model containing natural growth (model B) [24], and transduction-based feedback model (model C, Fig. 1–final model), were tested.…”
Section: Methodsmentioning
confidence: 99%
“…Other models, such as the collageninduced arthritis model, have also been used to evaluate antiinflammatory MAbs [39], and is still used today [40,41]. Data collected from preclinical pharmacology studies can be used to relate systemic MAb exposure to inflammation [42] as well as disease progression, which can subsequently be linked to human exposure and response [43,44].…”
Section: Animal Models Of Diseasementioning
confidence: 99%